Behavioral phenotyping of mice deficient for tumor necrosis factor - D. V. Fursenko; N. V. Khotskin; V. A. Kulikov; A. V. Kulikov (Вавиловский журнал генетики и селекции, 2015)
The tumor necrosis factor (TNF) is a cytokine exerting both homeostatic and pathophysiological roles in the central nervous system (CNS). It has been demonstrated that TNF plays roles in such diseases as Alzheimer’s disease, Parkinson’s disease and multiple sclerosis. Nevertheless, the role of TNF in the CNS under normal physiological conditions is poorly studied. A novel mouse strain with TNF deficiency (TNFKO) was developed in S.A. Nedospasov’s laboratory of Engelhardt Institute of Molecular Biology of the Russian Academy of Sciences on the C57Bl/6 (WT) background. In our study, we compared the behavior of TNFKO and WT adult mice in a battery of tests: open-field, elevated plus-maze and the forced-swim test. We showed that TNF deficiency had no effect on locomotor activity or exploration in the openfield test. At the same time, in this test, TNFKO mice spent more time in the center of the arena, but had a higher level of defecation and lower rearing duration. This result indicates that, in the openfield conditions, TNFKO mice show disorientation rather than anxiety-like behavior. There were no differences between TNFKO and WT in anxiety level in the elevated plus-maze test or in depressive-like behavior in the forcedswim test. These data suggest that TNF deficiency leads to changes in neurofunctional interactions that alter the mouse response to mild stress in the open-field test.